Early versus deferred endovenous ablation of superficial venous reflux in patients with venous ulceration: the EVRA RCT. - Gohel, Manjit S (Health Technol Assess, 2019)
BACKGROUND: Venous ulceration is a common and costly health-care issue worldwide, with poor healing rates greatly affecting patient quality of life. Compression bandaging has been shown to improve healing rates and reduce recurrence, but does not address the underlying cause, which is often superficial venous reflux. Surgical correction of the reflux reduces ulcer recurrence; however, the effect of early endovenous ablation of superficial venous reflux on ulcer healing is unclear. OBJECTIVES: To determine the clinical effectiveness and cost-effectiveness of compression therapy with early endovenous ablation of superficial venous reflux compared with compression therapy with deferred endovenous ablation in patients with venous ulceration. DESIGN: A pragmatic, two-arm, multicentre, parallel-group, open randomised controlled trial with a health economic evaluation. SETTING: Secondary care vascular centres in England. PARTICIPANTS: Patients aged ≥ 18 years with a venous leg ulcer of between 6 weeks' and 6 months' duration and an ankle-brachial pressure index of ≥ 0.8 who could tolerate compression and were deemed suitable for endovenous ablation of superficial venous reflux. INTERVENTIONS: Participants were randomised 1 : 1 to either early ablation (compression therapy and superficial endovenous ablation within 2 weeks of randomisation) or deferred ablation (compression therapy followed by endovenous ablation once the ulcer had healed). MAIN OUTCOME MEASURES: The primary outcome measure was time from randomisation to ulcer healing, confirmed by blinded assessment. Secondary outcomes included 24-week ulcer healing rates, ulcer-free time, clinical success (in addition to quality of life), costs and quality-adjusted life-years (QALYs). All analyses were performed on an intention-to-treat basis. RESULTS: A total of 450 participants were recruited (224 to early and 226 to deferred superficial endovenous ablation). Baseline characteristics were similar between the two groups. Time to ulcer healing was shorter in participants randomised to early superficial endovenous ablation than in those randomised to deferred ablation [hazard ratio 1.38, 95% confidence interval (CI) 1.13 to 1.68; p = 0.001]. Median time to ulcer healing was 56 (95% CI 49 to 66) days in the early ablation group and 82 (95% CI 69 to 92) days in the deferred ablation group. The ulcer healing rate at 24 weeks was 85.6% in the early ablation group, compared with 76.3% in the deferred ablation group. Median ulcer-free time was 306 [interquartile range (IQR) 240-328] days in the early ablation group and 278 (IQR 175-324) days in the deferred endovenous ablation group (p = 0.002). The most common complications of superficial endovenous ablation were pain and deep-vein thrombosis. Differences in repeated measures of Aberdeen Varicose Vein Questionnaire scores (p < 0.001), EuroQol-5 Dimensions index values (p = 0.03) and Short Form questionnaire-36 items body pain (p = 0.05) over the follow-up period were observed, in favour of early ablation. The mean difference in total costs between the early ablation and deferred ablation groups was £163 [standard error (SE) £318; p = 0.607]; however, there was a substantial and statistically significant gain in QALY over 1 year [mean difference between groups 0.041 (SE 0.017) QALYs; p = 0.017]. The incremental cost-effectiveness ratio of early ablation at 1 year was £3976 per QALY, with a high probability (89%) of being more cost-effective than deferred ablation at conventional UK decision-making thresholds (currently £20,000 per QALY). Sensitivity analyses using alternative statistical models give qualitatively similar results. LIMITATIONS: Only 7% of screened patients were recruited, treatment regimens varied significantly and technical success was assessed only in the early ablation group. CONCLUSIONS: Early endovenous ablation of superficial venous reflux, in addition to compression therapy and wound dressings, reduces the time to healing of venous leg ulcers, increases ulcer-free time and is highly likely to be cost-effective. FUTURE WORK: Longer-term follow-up is ongoing and will determine if early ablation will affect recurrence rates in the medium and long term. TRIAL REGISTRATION: Current Controlled Trials ISRCTN02335796. FUNDING: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 23, No. 24. See the NIHR Journals Library website for further project information.